Evaluación de la efectividad de los mecanismos de participación ciudadana para el desarrollo sostenible del Gobierno Autónomo Descentralizado Parroquial Rural de Membrillo - Sacón Sabando, Karina Vanessa (2025)
This research aims to evaluate the effectiveness of the citizen participation mechanisms for the sustainable development of the Rural Parochial Decentralized Autonomous Government of Membrillo, in which a low citizen participation has been identified due to the lack of knowledge of these mechanisms and the deficiencies in the communication between the GAD and the community, based on this diagnosis the main purpose was to identify areas of improvement and propose a strategic plan that promotes a greater inclusion and active participation of the inhabitants. Through a mixed approach, interviews were carried out with the president of the GAD and surveys with a representative sample of the local population (347 citizens), complemented with an exhaustive analysis of current regulations and bibliographic studies, the results revealed that, although there are mechanisms established, a high percentage of the population is unaware of their performance, which limits their active participation. The improvement plan, designed with the 5W1H methodology, includes information campaigns, training workshops and measures to facilitate access to participatory processes, with a focus on territorial equity and sustainability, its implementation seeks to strengthen transparency and the relationship between the GAD and the citizens. It is concluded that citizen participation is an essential pillar for governance and sustainable development, and its strengthening requires joint efforts between authorities and inhabitants. This research provides practical and theoretical tools that can be replicated in other rural contexts to promote more inclusive management and democratic.